2019
DOI: 10.1002/gch2.201800117
|View full text |Cite
|
Sign up to set email alerts
|

Bioinspired Soot‐Deposited Janus Fabrics for Sustainable Solar Steam Generation with Salt‐Rejection

Abstract: Inspired by lotus leaves, self‐floating Janus cotton fabric is successfully fabricated for solar steam generation with salt‐rejecting property. The layer‐selective soot‐deposited fabrics not only act as a solar absorber but also provide the required superhydrophobicity for floating on the water. With a polyester protector, the prepared Janus evaporator exhibits a sustainable evaporation rate of 1.375 kW m −2 h −1 and an efficiency of 86.3% under 1 sun (1 kW m … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(49 citation statements)
references
References 47 publications
1
48
0
Order By: Relevance
“…For example, the difference in structure can be used to achieve the purpose of hydrophobic, such as the use of soot and cotton fiber to interweave to achieve a hydrophobic system. [ 128 ] Experiments showed that under 5 h of simulated sunlight, no salt was produced on the surface of the evaporator after 20 d. The prepared Janus evaporator also had a continuous evaporation capacity of 1.375 kg m −2 h −1 and an efficiency of 86.3% during 1 d under 1 kW m −2 radiation. It also performed well under low‐intensity and oblique radiation.…”
Section: Salt Mitigation Strategiesmentioning
confidence: 99%
“…For example, the difference in structure can be used to achieve the purpose of hydrophobic, such as the use of soot and cotton fiber to interweave to achieve a hydrophobic system. [ 128 ] Experiments showed that under 5 h of simulated sunlight, no salt was produced on the surface of the evaporator after 20 d. The prepared Janus evaporator also had a continuous evaporation capacity of 1.375 kg m −2 h −1 and an efficiency of 86.3% during 1 d under 1 kW m −2 radiation. It also performed well under low‐intensity and oblique radiation.…”
Section: Salt Mitigation Strategiesmentioning
confidence: 99%
“…Owing to the pores among fibers and their hydrophilicity, the cotton fabric enables fast water transport via the capillary effect (Figure 10A). Different photothermal materials can be anchored onto the cotton fabric for solar evaporation, such as PPy via in-situ polymerization (Figure 10B, C) [6,18] , MoS 2 via hydrothermal self-growth method [106] , and soot via exposure to candle flame [105,107] . The rough surface of cotton fabric provides a large surface area for loading photothermal materials and increases the light reflection among photothermal materials.…”
Section: 6mentioning
confidence: 99%
“…[104] Various architectures can be obtained in cotton fabric by simply cutting using scissors [27]. The price for plain cotton is about $0.55 m −2 ,[105] which makes it viable for practical applications. Owing to the pores among fibers and their hydrophilicity, the cotton fabric enables fast water transport via the capillary effect (Figure 10A).…”
Section: Applications Of Cellulosic Nanomaterials In Solar Steam Generationmentioning
confidence: 99%
“…Better heat regulation may reduce thermal loss to the environment to a great extent, thereby collecting more solar energy and converting it directly into the enthalpy of liquid evaporation and improving the efficiency of thermal evaporation. In order to suppress radiation loss, the ideal solar absorber must possess low thermal emissivity and high incident light absorption, which can be realised by high reflectance at the long-wave infrared region [54]. The heat loss of a solar absorber is caused by heat radiation, which increases at high temperatures.…”
Section: Solar-thermal Conversion Mechanisms and Evaluation Standardsmentioning
confidence: 99%